Analysis of the Power Blackout in the Marmara Earthquake - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY, 2010)
B. Oral, F. Donmez. Analysis of the Power Blackout in the Marmara Earthquake // Electronics and Electrical Engineering. - Kaunas: Technologija, 2010. - No. 8(104). - P. 77-80. An earthquake occurred on August 17, 1999 in Turkey and the Turkish Power System was adversely affected by the earthquake. Therefore, the power system collapsed. In this study, it was examined the power blackout on the system and technically analyzed by MATLAB simulation program. Voltage profiles of the region are shown in graphics. Ill. 6, bibl. 12, tabl. 1 (in English; abstracts in English, Russian and Lithuanian).